Japanese Encephalitis antibody detection from blood samples of domestic dogs and cats in Peninsular Malaysia - Erandika Perera, Palliyage Don Heshini (2016)
Japanese Encephalitis Virus (JEV), of the Flaviviridae family, is a known cause of acute encephalitis in humans throughout South East Asia. It is transmitted through mosquito vector, with Culex tritaeniorhynchus being the vector most associated with spread of the disease. It has been identified in various animals, including in cats and dogs, however, there has been no study done in Malaysia investigating JEV in cats and dogs. The purpose of this study is to identify the presence of JEV antibodies in cats and dogs in Malaysia, using Enzyme Linked Immunosorbent Assay (ELISA). Methods Two to five ml of blood was collected from shelter cats and dogs and two ml of serum was collected from diagnostic samples of cat patients to University Veterinary Hospital, with consent. Information collected for each animal included age, sex, health status, management and environment through observation and patient records. Three ELISA assays were performed, following protocol provided by the manufacturer (SunRed Biotechnology Cat JE IgG ELISA kit and MyBioSource Dog JE IgG ELISA kit). The tests were carried out with all samples in duplicate and the positive and negative samples were identified by calculating the critical value as instructed by the manufacturer. Results The results revealed that 15% of 40 pet cats, 17.7% of shelter cats and 80% of shelter dogs were positive for JEV antibodies, with shelter dogs being four times more likely to be seropositive than shelter cats. Fisher’s Exact Test (p < 0.05) was used to compare results and possible factors affecting the result, from patient information, revealing that there appeared to be no significant relation between sex, health, management, age and location. Conclusion Dogs and cats in Malaysia are seropositive for JEV antibodies and can be used as sentinels.